Rawls and religion : the case for political liberalism - Dombrowski, Daniel A. (Albany : State University of New York Press, 2001)
Annotation Not only are scholars incorrect when they assume 20th-century political philosopher John Rawls is not interested in the relationship between politics and religion, contends Dombrowski (philosophy, Seattle U.), but in fact his treatment shows that the relationship is at the core of the problem that liberalism has for centuries meant to solve. He uses Rawl's thought to examine abortion, fundamentalism as a growth industry, the perceived decline of secular culture, and other controversial issues. Annotation copyrighted by Book News Inc., Portland, OR.
pt. 1. Theory -- A brief history -- The original position -- The reasonable and the rational -- The ancients and the moderns -- The common good -- Methodological considerations -- pt. 2. Practice -- Theory to practice -- Partially inclusive public reason -- Race, sex, and abortion -- War, disobedience, and elections -- Animals and marginal cases.
Includes bibliographical references (pages 181-188) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Rawls, John, -- 1921-2002 -- Contributions in political science; Rawls, John, -- 1921- -- Pensée politique et sociale; Rawls, John, -- 1921- -- Et le libéralisme.; Rawls, John, -- 1921- -- Morale; Rawls, John, -- 1921- -- Religion; Rawls, John, -- 1921-2002; Rawls, John -- 1921-2002; Rawls, John; Liberalism; Religion and politics; Religion et politique; Libéralisme.; liberalism; POLITICAL SCIENCE -- Political Process -- Political Advocacy; Liberalism; Political science; Religion and politics; Liberalismus; Politik; Politische Philosophie; Religion; Politische Ethik; Godsdienst; Politieke filosofie; Liberalisme; Electronic book